Acoustics of ping-pong: Vibroacoustic analysis of table tennis rackets and balls - Russell, D. A. (Journal of Sports Sciences, 2018)
The sound resulting from the impact of a table tennis racket and ball can influence a player`s perception of equipment quality in addition to providing clues to personal performance. This study explores the vibrational modes of both racket and ball and how those modes contribute to the impact sound. Experimental modal analysis reveals that the racket exhibits a large number of structural vibration modes typical of elliptical plates. Acoustic analysis reveals that two of those structural modes dominate the sound produced by the ball-paddle impact. The rubber padding provides some damping and a significant mass loading to the racket vibrations. The hollow cellulose nitrate balls exhibit vibrational modes typical of a hollow spherical shell, starting with frequencies around 5920 Hz. Experimental frequencies confirm theoretical and computational models. However, the contact time between racket and ball is long enough that the lowest acoustic modes of the ball do not contribute to the radiated sound. Instead, acoustic analysis suggests that the ball appears to radiate sound at a much higher frequency sound (8.5-12 kHz) most likely due to snap-through after buckling common to spherical shells undergoing deformation while impacting a rigid surface at high speeds.